2017
DOI: 10.1113/jp273726
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic withdrawal increases heart rate after 2 weeks at 3454 m altitude

Abstract: Chronic hypoxia increases resting heart rate (HR), but the underlying mechanism remains incompletely understood. We investigated the relative contributions of the sympathetic and parasympathetic nervous systems, along with potential non-autonomic mechanisms, by individual and combined pharmacological inhibition of muscarinic and/or β-adrenergic receptors. In seven healthy lowlanders, resting HR was determined at sea level (SL) and after 15-18 days of exposure to 3454 m high altitude (HA) without drug intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The increase in resting heart rate during exposure to 6022 m and 7042 m, as observed in the present study, corresponds with previous data (Lundby & van Hall, ) and has been attributed mostly to high altitude‐related sympathoexcitation and parasympathetic withdrawal (Siebenmann et al . ). Cardiac output at rest is expected to decrease towards SL values after an initial increase in well‐acclimatized lowlanders at moderate altitude (Hilty et al .…”
Section: Discussionmentioning
confidence: 97%
“…The increase in resting heart rate during exposure to 6022 m and 7042 m, as observed in the present study, corresponds with previous data (Lundby & van Hall, ) and has been attributed mostly to high altitude‐related sympathoexcitation and parasympathetic withdrawal (Siebenmann et al . ). Cardiac output at rest is expected to decrease towards SL values after an initial increase in well‐acclimatized lowlanders at moderate altitude (Hilty et al .…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, Obrezchikova et al (2000) also showed that during hypoxic challenges (hypobaric hypoxic chamber), the parasympathetic modulation is decreased in conscious freely moving rats. Similarly, it has been shown that chronic exposure to High-Altitude, causes increases in HR due to parasympathetic withdrawal ( Dhar et al, 2014 ; Siebenmann et al, 2017 ). Something interesting to note, is that the parasympathetic withdrawal could persist after one month of high-altitude exposure ( Farinelli et al, 1994 ; Dhar et al, 2014 ).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, in contrast to baroreflex control of MSNA, cardiac baroreflex sensitivity is closely related to vagal activity, and increases in resting heart rate at HA are proposed to be mediated by cardiac vagal withdrawal with minimal or no effect of sympathetic activity (Siebenmann et al . ). Furthermore, as the authors mentioned, erythropoietin production, systemic inflammation and oxidative stress could also explain the study findings.…”
mentioning
confidence: 97%